The lyrical hero of Vladas Grybas - Trimonis, Rytis (Literatūra, 1970)
This article is an attempt to reveal the characteristic features of the lyrical hero in the poetry of Vladas Grybas (1927-1954), one of the most typical representatives of the post-war generation of Soviet Lithuanian poets.The personality of the poet developed under the conditions of sharp class struggle when life itself made the poet take a straightforward and uncompromised position in the struggle. It is natural, therefore, that the outlook and the character of the poet found a most vivid reflection in his lyrical hero.Self-exacting and wholly devoted to Socialism, the lyrical hero of V. Grybas calls upon his countrymen with ardent words and emotionally inspirited declaration to construct a new life. He lives the life of a fighter, inflicting constant defeats to his ideological enemies with the sharp weapon of letters. „Heroic Lyrics", glorifying the victory of collectivization in Lithuania, determines the harmony of thought and passion in the lyrical hero, the interlacing of his personal and public interests which found expression in the first book of verses by V. Grybas „By Direct Laying" as early as 1949. The portraits of builders of the new life are depicted only in general outline serving the aim of showing the lyrical hero's attitude towards life in another aspect.Besides the ideals of fight and work, the ideal of creation is peculiar to the lyrical hero of V. Grybas as well. He sees the role of art, and of poetry in particular, in consolidating the victory of Socialism and ideas of the Communist Party.Revealing the beauty of nature the poet displays the aesthetical ideal of his hero, particularly in his last verses. His best landscape and love verses show the inner beauty of the lyrical hero, the profoundness of his feelings.In the satirical rhymes the lyrical hero speaks as a prosecutor, a bitter enemy of narrow-mindedness and inactivity. It is a new kind of expression of the hero's character.The lyrical hero of V. Grybas is a direct successor to the heroes of Mayakovsky and Montvila, an incarnation of a fighter, of the poet himself as he was known in the post-war Lithuanian poetry.
Keywords: -